High School English Language Learners’ Experiences and Perceptions of Independent Online Content-Based Instruction - Lee, Kent; Abbott, Marilyn (Language and Literacy / Langue et littératie, 2025)
Although technology-enhanced learning has exploded, limited research has examined English language learners’ (ELLs) experiences and perceptions of independent online content-based second language learning. To fill this gap, an innovative web application was designed to improve ELLs’ grade 10 science content and English language learning. Fifty-six high school ELLs independently completed 30 online modules and then responded to a 12-item questionnaire about the web application, the module content, and their learning. An applied thematic analysis of their responses revealed several benefits and a few challenges that provide insights for the development and improvement of independent online content-based learning for high school ELLs.